Math, asked by sa862335gmail, 3 months ago

2^-3×4^-1 simplify this question​

Answers

Answered by siaditya63
0

Answer:

khud answer nical lo because I don't know the answer

Answered by MrMonarque
112

Solution:-

→\;( {2})^{ - 3}  \times ( {4})^{ - 1}  \\ →\; ({2})^{ - 3}  \times  {2}^{(2)( - 1)}  \\ →\; {2}^{ (- 3 )+ ( - 2)}  \\→\; {2}^{ - 5}  \\→\;  \frac{1}{ ({2})^{5} } \\→\;  \frac{1}{32}

  • Value ☞ \Large\red{\bold{\frac{1}{32}}}

a^b×a^c = a^(bc)

a^(-1) = 1/[a^(1)]

\boxed{\tt{@MrMonarque}}

Hope It Helps You ✌️

Similar questions